BREAKING BOUNDARIES: DEVELOPING CUSTOMIZED LEARNING MATERIALS FOR SENIOR HIGH SCHOOL WITH EMANCIPATED CURRICULUM DESIGN - Kinanti, Gusti Ayu Anggita; Kerti Nitiasih, Putu; Mahayanti, Ni Wayan Surya (Universitas Suryakancana, 2025)
This study aims to develop differentiated English learning materials in the form of books for 10th-grade students of Senior High School in first semesters based on using an Emancipated Curriculum. This research uses the Design and Development model by Richey and Klein (2014) as the basis of the methodology. The design and Development model has four stages: analysis, design, development, and evaluation. The data obtained from this study used instruments in the form of interviews, questionnaires, and document analysis. The quality of the product received excellent from two experts, and this product is valid for use in differentiated learning-based learning styles for teachers and students. The results of this research show that differentiated English learning materials in the form of books for 10th-grade students of Senior High School in first semesters based on using an Emancipated Curriculum can help teachers in differentiated teaching and make it easier for students to learn according to their learning style